Collaboration in planning: The Geodesign approach - Campagna, Michele; Steinitz, Carl; Di Cesare, Elisabetta Anna; Cocco, Chiara; Ballal, Hrishikesh; Canfield, Tess (Rozwój Regionalny i Polityka Regionalna, 2016)
This paper proposes a critical review of Geodesign methods and techniques which can be used to carry out collaborative design in participatory processes. The case study of a Geodesign workshop held in 2016 Cagliari (Italy) shows how it is possible to involve teams of members of the community in what is perhaps the most critical phase of a spatial planning process that is putting knowledge into action through the collaborative design of future change alternatives, and their choice based on negotiation. In addition, a discussion of further potential of the Geodesign approach in public participation is discussed with reference to both knowledge creation and community value and preferences accounting.